A dangerous pedagogy of discomfort: Redressing racism in theology education - Dames, Gordon Ernest (HTS teologiese studies, 2019)
This article aims to illustrate how racism could be addressed. Three pedagogies – a dangerous pedagogy as courageous dialogue, a pedagogy of discomfort and a critical pedagogy – are presented as examples to reframe the issue of racism. The contribution of James Cone is applied as a broad descriptive theoretical framework. Cone’s views in this article resonate with the history of contemporary racism in South Africa and will therefore be juxtaposed by the contribution of South African theologians. A fourth pedagogy, namely, a pedagogy of freedom and healing, is introduced to address gaps in the first three pedagogies. The objective is to realise freedom or healing between people of different races.